(untitled) (Scientific journal of the Fergana State University, 2024)
This article analyzes the botanical, biological and medicinal properties, as well as the role in folk medicine of the Allium cepa (onion) plant growing in the Fergana Valley. The main attention was paid to the study of the chemical composition, especially the content of water-soluble vitamins and their importance in the treatment of certain human diseases and a quantitative analysis of vitamins in the bark of the Allium cepa plant was carried out using the JSS method.